FEATURES OF FORMATION OF EXTRA-BUDGETARY FUNDS OF BUDGET ORGANIZATIONS ON THE BASIS OF ENTREPRENEURSHIP (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article discusses the features of the formation of extra -budgetary funds of budgetary organizations and their formation on the basis of entrepreneurship. Proposals have been made on the formation of extra-budgetary funds of budgetary organizations in the manner of entrepreneurship and the improvement of their accounting. systematized the stages of development of accounting in budgetary institutions from the point of view of extra-budgetary activities, assessed the local practice of accounting for extra-budgetary funds of institutions financed from the budget. justified the classification of extra-budgetary funds of institutions financed from the budget, the definition of the concept of "target funds". Budget institutions performing business activities are participants in market relations along with other organizational and legal entities, they provide public services, sell goods, perform work, and at the same time receive expenses and income. The Budget Code of the Republic of Uzbekistan has not developed a clear description of the procedure for the formation of revenues and expenses of the budget institution. As a result, keeping budget accounts in practice causes many difficulties, especially transactions related to the implementation of business activities. Therefore, it is necessary to systematize and significantly unify the accounting of transactions related to extra-budgetary funds, as well as to solve the currently controversial issue of recognizing income and expenses from the business activities of budget institutions. Unlike commercial enterprises, the task of accounting for extra-budgetary funds of budgetary institutions is not only to provide information for the purpose of making investment and management decisions, but also to ensure control over the activities of institutions by state bodies. Reforming the budget account is an urgent task in order to ensure the transparency of business activity and increase its efficiency. Now the situation is such that the information in the legally established financial reporting network is not enough for the management of the institution to make informed management decisions and for the founder to control extra-budgetary activities. The current stage of the development of budget accounting of budget organizations includes its two traditional sectors - budget execution accounting and unification of accounting in budget institutions and transition to a single plan of accounts for budget accounting. Budget accounting information and, as a result, the state balance is formed based on the accounting of each individual budget institution, which allows local and international users to present information on a qualitatively new basis. The information describing the state activity includes extra-budgetary indicators of institutions financed from different levels of budgets.